STUDENTS' PSYCHOLOGICAL PROBLEMS IN ENGLISH SPEAKING PERFORMANCE - Rosita, Aulia (ELP (Journal of English Language Pedagogy), 2024)
This study explores the psychological factors hindering English speaking performance among eleventh graders at MAN 2 Bukittinggi, Indonesia. A closed questionnaire assessed five key factors: anxiety, shame, lack of self-confidence, lack of motivation, and fear of making mistakes. The survey was administered to a sample of 55 students from a population of 223. Results revealed anxiety as the most prevalent issue, affecting 86.1% of students. Furthermore, a significant portion of students also reported experiencing a lack of confidence (74.1%), shyness (77.2%), and fear of making mistakes (77.5%), contributing to reduced motivation (70.1%) for learning English. Identifying anxiety as the primary psychological barrier can inform the development of teaching strategies that address student anxieties and enhance English speaking performance.